Interactive Multimedia Based on the PjBL Model with Public Health Orientation Assisted by Articulate Storyline 3 - Ni Luh Trisna Ari Utami; I Gede Margunayasa; Ni Wayan Rati (Universitas Pendidikan Ganesha, 2023)
Lack of learning media and models and declining learning outcomes in science learning. This research aims to develop PjBL-based Interactive Multimedia with a public health orientation on Human Respiratory System material for class V elementary school that is feasible, practical, and effective for improving student learning outcomes. This type of research is Research and Development with the ADDIE model. The subjects of this research were two media experts, two material experts, three teachers and six students, and 1 class V group of 34 students. The data analysis techniques used are descriptive, qualitative, and quantitative. The data collection methods were questionnaires and tests with instruments such as rating scale sheets and multiple-choice tests. The research design used was a pre-experimental, one-shot case study. The research results show that the media prototype developed consists of 3 main parts, namely the opening, initial, and prominent displays. The media suitability index is categorized as high, and the average material test score is very decent. The results of the practicality test by teachers are high, and the practicality test by students are categorized as very good. Interactive Multimedia based on the PjBL model was declared effective in improving the learning outcomes of fifth-grade elementary school students. It was concluded that the media developed was feasible, practical, and effective in improving student learning outcomes in the Human Respiratory System material for class V elementary school.